2022
DOI: 10.3390/plants11162105
|View full text |Cite
|
Sign up to set email alerts
|

QTL Analysis for Bread Wheat Seed Size, Shape and Color Characteristics Estimated by Digital Image Processing

Abstract: The size, shape, and color of wheat seeds are important traits that are associated with yield and flour quality (size, shape), nutritional value, and pre-harvest sprouting (coat color). These traits are under multigenic control, and to dissect their molecular and genetic basis, quantitative trait loci (QTL) analysis is used. We evaluated 114 recombinant inbred lines (RILs) in a bi-parental RIL mapping population (the International Triticeae Mapping Initiative, ITMI/MP) grown in 2014 season. We used digital ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 98 publications
1
4
1
Order By: Relevance
“…The QTL on chromosome 3D, which explained more than 50% of the phenotypic variation, was consistent with the location of R-1/TaMyb10(Himi et al 2011), which is associated with the PHS-3D-mediated resistance to pre-harvest sprouting(Lang et al 2021). Few QTLs for SCC were detected on chromosome 5B, with the exception of the QTLs related to seed color characteristics on chromosome 5BL(Arif et al 2022).…”
supporting
confidence: 74%
“…The QTL on chromosome 3D, which explained more than 50% of the phenotypic variation, was consistent with the location of R-1/TaMyb10(Himi et al 2011), which is associated with the PHS-3D-mediated resistance to pre-harvest sprouting(Lang et al 2021). Few QTLs for SCC were detected on chromosome 5B, with the exception of the QTLs related to seed color characteristics on chromosome 5BL(Arif et al 2022).…”
supporting
confidence: 74%
“…We hypothesize the presence of genes within this locus affecting grain color development. Our study's grain color loci did not coincide with those identified by Arif et al, who employed the same seed color estimation method [51]. However, the locus containing the TraesCS7B03G1296800 gene on chromosome 7B, encoding PSY, was previously associated with flour and endosperm color [52,53].…”
Section: Comparing the Localization Of Putative Qtl With Existing Datacontrasting
confidence: 48%
“…The digital image processing and color analysis was performed using Seed-Counter application, version for desktop PC [37,38]. A single image per accession was used, since previous work demonstrated no significant differences between mean values of the seed traits obtained for several replicates [51]. Seeds were imaged before sowing in 2021.…”
Section: Grain Color Traits Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative is the use of digital RGB cameras that produce high-quality images with high spatial and color resolution (Afonnikov et al, 2016;Li et al, 2020;Kolhar, Jagtap, 2023). In this regard, methods for estimating color and textural characteristics of cereal grains based on the analysis of twodimensional images acquired by digital cameras or scanners have recently been intensively developed in the field of grain phenotyping (Komyshev et al, 2020;Sharma et al, 2021;Afonnikov et al, 2022;Arif et al, 2022;Khojastehnazhand, Roostaei, 2022;Wang, Su, 2022).…”
Section: Introductionmentioning
confidence: 99%